Short-term acidification promotes diverse iron acquisition and conservation mechanisms in upwelling-associated phytoplankton - Robert H. Lampe; Tyler H. Coale; Kiefer O. Forsch; Loay J. Jabre; Samuel Kekuewa; Erin M. Bertrand; Aleš Horák; Miroslav Oborník; Ariel J. Rabines; Elden Rowland; Hong Zheng; Andreas J. Andersson; et al. (Nature Communications, 2023)
Abstract Coastal upwelling regions are among the most productive marine ecosystems but may be threatened by amplified ocean acidification. Increased acidification is hypothesized to reduce iron bioavailability for phytoplankton thereby expanding iron limitation and impacting primary production. Here we show from community to molecular levels that phytoplankton in an upwelling region respond to short-term acidification exposure with iron uptake pathways and strategies that reduce cellular iron demand. A combined physiological and multi-omics approach was applied to trace metal clean incubations that introduced 1200 ppm CO2 for up to four days. Although variable, molecular-level responses indicate a prioritization of iron uptake pathways that are less hindered by acidification and reductions in iron utilization. Growth, nutrient uptake, and community compositions remained largely unaffected suggesting that these mechanisms may confer short-term resistance to acidification; however, we speculate that cellular iron demand is only temporarily satisfied, and longer-term acidification exposure without increased iron inputs may result in increased iron stress.